Economic progress and prospects in the Third World : lessons of development experience since 1945 - Singer, H. W. (E. Elgar, 1993)
Combines a summary of development progress over the last 40 years with case studies of two major developing countries, Nigeria and India. The book distinguishes three main phases, the "Golden Age" of the 1950s and 60s, the illusionary debt-led growth of the 1970s and the "Lost Decade" of the 1980s